Predictability of European winter 2021/2022: Influence of La Niña and stratospheric polar vortex - Peter McLean; Chris Bulmer; Paul Davies; Nick Dunstone; Margaret Gordon; Sarah Ineson; Jason Kelly; Jamie Kettleborough; Jeff Knight; Julia Florence Lockwood; Adam A. Scaife; Doug Smith; et al. (Atmospheric Science Letters)
Abstract The Northern Hemisphere winter of 2021/2022 exhibited a positive North Atlantic Oscillation (NAO) which led to largely mild and wet conditions for Northern Europe. A moderate La Niña in the tropical Pacific and a stronger than average stratospheric polar vortex together explained the observed anomalies over the winter. Winter 2021/2022 was well predicted in general by seasonal forecast systems. The ensemble mean indicated a positive winter NAO and the forecast spread of forecasts from the Met Office GloSea6 seasonal prediction system spanned the observed mean sea level pressure anomaly for the whole winter and the individual months. However, December showed the largest departure from the mean of the forecast which is consistent with evidence from previous work that early winter ENSO teleconnections are too weak in model predictions. Nevertheless, around one in four members captured the negative NAO pattern in December. The strong pressure gradient and positive NAO predicted for the latter part of the winter allowed successful warning of the possibility of above average storminess and strong winds which occurred in February 2022. This is potentially useful information for the energy sector who increasingly rely on wind power and the insurance industry for warning of storm damage.